Adsorption and separations for methane, carbon dioxide, nitrogen and oxygen gases - Li, Peiyuan (University of Ottawa (Canada), 2007)
Adsorption behaviour of different gases were studied in this work for adsorption and adsorbent membrane separations for flue gas, natural gas and landfill gas applications. Pure adsorption kinetics and equilibrium of CO2, N2, CH4 and O2 with beta-zeolite adsorbent, and CO 2 and N2 with adsorbents silicalite, NaY and 13X zeolites were studied by using concentration pulse chromatography. Adsorption Henry's Law constants, heats of adsorption, micro-pore diffusion coefficients and corresponding activation energies were determined experimentally and the three different mass transfer mechanisms were discussed. Ideal separation factors were obtained for the adsorption separation applications of the gases studied. Micro-pore diffusion resistance is the definite dominant mass transfer mechanism for most of the adsorbents and separations studied. Adsorption separations of CO2/N2, CO2/ CH4 and CH4/N2 on silicalite were studied by using constant volume and concentration pulse chromatographic techniques. Mixture adsorption isotherms for the binary systems were determined experimentally by using three binary concentration pulse methods. Corresponding x-y adsorption phase diagrams and realistic separation factors were obtained from these experimental binary adsorption isotherms. The results showed that silicalite is a promising adsorbent for the separation of carbon dioxide and nitrogen. Thermodynamic consistency tests between pure and binary gas adsorption systems were performed and results showed reasonable consistency. Breakthrough curves for dynamic adsorption separation of CO2/CH 4, CO2/N2 and CH4/N2, gases with silicalite were determined. Parametric studies, as well as economic assessments were carried out for these separations, using adsorption columns packed with silicalite. Separations of CO2/CH4, CO2/N2 and CH4/N2 gases with MFI zeolite membrane and separation of CO2/N2 gases with two silicone rubber membranes were also studied in this work. Separation factors and permeabilities were measured, adsorption behaviours were analyzed, and separation process mechanisms were discussed. It was concluded that adsorption plays an important role in the separations of these gases with MFI zeolite membrane and silicone rubber membranes.
Keywords: Engineering, Chemical.